Pengaruh CR dan DER terhadap ROA pada Perusahaan Subsektor Logistics and Forwarding yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020 - Hari Fauzan; Furi Indriyani; Rohani Lestari (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The pandemic and price competition are the main reasons why Logistics and Forwarding companies are approaching bankruptcy. This research aims to determine the influence of the Current Ratio and Debt To Equity Ratio on Return on Assets in Logistics and Forwarding Subsector Companies Listed on the Indonesia Stock Exchange in 2019-2022. The research method used in this research is quantitative research with a descriptive approach. The data used in this research is secondary data obtained from the financial reports of Logistics and Forwarding Subsector companies published on the Indonesia Stock Exchange website. The data analysis used in this research is descriptive statistical analysis, classical assumptions, multiple linear regression, hypothesis testing used is the T test and F test, and the coefficient of determination. Based on the results of this test, it shows that partially the Current Ratio variable has a positive and significant effect on Return On Assets. value (tcount 2.304 > 1.676) and value (significant 0.026 < 0.05) and the Debt To Equity Ratio variable do not have a positive and significant effect on the Return On Asset value (tcount 1.329 < 1.676) and the value is significant (0.190 > 0.05). Simultaneously, the Current Ratio and Debt To Equity Ratio have an effect on Return On Assets, the f value is 3.470 > 2.80) and value (significant 0.039 < 0.05)